Proposal for Psychomotor Development According to A.R. Luria’s Conception: New Data in Mexico - Juan Pelayo González, H; Solovieva, Y (KnE Life Sciences, 2018)
The aim of this work was to test a program for psychomotor development based on Luria´s concept of three functional brain units or blocks and the necessity of stimulation of the first functional unit in early childhood. Stimulation of subcortical systems associated with psychomotor and cognitive regulation may help to set the basis for positive functioning of the cerebral cortex in the coming years. Vestibular exercises and proprioceptive stimulation were used. All exercises included significant communicative activity as described by Vigotsky and Lisina, which provide positive direct emotional contact between adult and child. Thirty-six babies with neurological risk were included in the study, along with their parents. After 300 days in the stimulation program, all the children presented positive functional development. We conclude that positive effects of these programs for correction and psychological development may be achieved during the first year of life. Keywords: neurological risk, emotional contact, joint activity, vestibular stimulation